2006
DOI: 10.4049/jimmunol.177.4.2294
|View full text |Cite
|
Sign up to set email alerts
|

Constitutively Active β-Catenin Promotes Expansion of Multipotent Hematopoietic Progenitors in Culture

Abstract: This study was designed to investigate one component of the Wnt/β-catenin signaling pathway that has been implicated in stem cell self-renewal. Retroviral-mediated introduction of stable β-catenin to primitive murine bone marrow cells allowed the expansion of multipotential c-KitlowSca-1low/−CD19− CD11b/Mac-1−Flk-2−CD43+AA4.1+NK1.1−CD3−CD11c−Gr-1−CD45R/B220+ cells in the presence of stromal cells and cytokines. They generated myeloid, T, and B lineage lymphoid cells in culture, but had no T lymphopoietic poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 58 publications
3
55
0
Order By: Relevance
“…Indeed different ␤-catenin gain-of-function studies yielded different results probably reflecting the effect of different dosages of activation of the pathway. 6,8,9 The notion that correct levels of Wnt signaling are critical in inducing a self-renewal type of expansion in HSC 45 is also supported by experiments from Baba et al, 46,47 who showed that it is possible to induce some stem cell characteristics in committed progenitors by ectopic expression of stable ␤-catenin. However, such progenitors did not reconstitute T cells when transplanted to immunodeficient mice, showing again that a very strong signal that bypasses all negative regulatory steps of the Wnt-signaling cascade such as given by stabilized ␤-catenin cannot mimic events triggered by tightly regulated physiological Wnt signals.…”
Section: Discussionmentioning
confidence: 53%
“…Indeed different ␤-catenin gain-of-function studies yielded different results probably reflecting the effect of different dosages of activation of the pathway. 6,8,9 The notion that correct levels of Wnt signaling are critical in inducing a self-renewal type of expansion in HSC 45 is also supported by experiments from Baba et al, 46,47 who showed that it is possible to induce some stem cell characteristics in committed progenitors by ectopic expression of stable ␤-catenin. However, such progenitors did not reconstitute T cells when transplanted to immunodeficient mice, showing again that a very strong signal that bypasses all negative regulatory steps of the Wnt-signaling cascade such as given by stabilized ␤-catenin cannot mimic events triggered by tightly regulated physiological Wnt signals.…”
Section: Discussionmentioning
confidence: 53%
“…The serial BM from WT and β-catenin CKO transplantation data (summarized in Figure 5C) demonstrate that β-catenin contributes to HSC maintenance throughout successive transplants of Gsk3-deficient BM cells. These data, taken together with previously published observations from others (11,(20)(21)(22)(23)(24)(25)(26)(27)(28), support a positive role for the Wnt/β-catenin pathway in HSC maintenance in the context of reduced GSK-3 activity, but also suggest that an additional GSK-3-regulated pathway plays a distinct and possibly antagonistic role in HSC maintenance.…”
Section: Gsk3 Loss Of Function In Hematopoietic Cells Therapeutic LImentioning
confidence: 64%
“…A role for Wnt signaling in hematopoiesis is supported by observations that Wnt ligands enhance proliferation of HSCs ex vivo (20)(21)(22) and that Wnt antagonists inhibit HSC proliferation and reconstitution (23,24). In addition, overexpression of stabilized β-catenin promotes HSC self renewal and proliferation ex vivo under certain conditions (20)(21)(22)(23)25), and conditional deletion of β-catenin using vav-cre impairs HSC function in competitive repopulation assays (26). Furthermore, long-term reconstituting capacity in serial transplants is impaired in HSCs recovered from fetal liver of Wnt3a KO embryos (20-23, 25, 27) or from adults overexpressing the Wnt inhibitor Dkk in the hematopoietic niche (28), which suggests that Wnt signaling is required to maintain the long-term repopulating activity of HSCs.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…However, others reported that purified Wnt protein in vitro (5) or inhibition of GSK3␤ in vivo (6) promotes the self-renewal of HSCs. Baba et al (7,8) showed that constitutive activation of ␤-catenin impaired multilineage differentiation, whereas others found that expression of constitutively active ␤-catenin in hematopoietic cells in vivo leads to loss of HSC repopulation and multilineage differentiation block (9,10). The role of ␤-catenin in the regulation of cell proliferation and apoptosis is cell context-dependent.…”
mentioning
confidence: 99%